2018
DOI: 10.26442/terarkh201890689-91
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of chronic kidney disease patients on renal replacement therapy

Abstract: The study demonstrated the results of the comparative analysis of various types of renal replacement therapy effects on the quality of life patients with terminal stage of chronic kidney disease on the basis of standardized questionnaires. It has been shown that the quality of life is significantly improved after a kidney transplantation. At the same time, it has also been found that the introduction of home dialysis, epoetins, active metabolites of vitamin D, calcimimetics in the clinic care expanded the oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…Considering OHRQoL to be a part of HRQoL [7,8,47], an interrelationship between these parameters seems plausible in patients under RRT. It is known that general HRQoL is reduced in patients under RRT, especially those under HD [4][5][6]. Therefore, impairment of HRQoL, and in consequence OHRQoL, is conceivable, although it cannot be strongly confirmed by available studies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering OHRQoL to be a part of HRQoL [7,8,47], an interrelationship between these parameters seems plausible in patients under RRT. It is known that general HRQoL is reduced in patients under RRT, especially those under HD [4][5][6]. Therefore, impairment of HRQoL, and in consequence OHRQoL, is conceivable, although it cannot be strongly confirmed by available studies.…”
Section: Discussionmentioning
confidence: 98%
“…The improvements in therapeutic measures during RRT and the decrease in mortality might lead to a change in the major challenge of care for these patients; thus, patient-related outcomes such as improving patients' well-being and quality of life are of increasing importance [1,3,4]. It is known that healthrelated quality of life (HRQoL) is often reduced by RRT, especially for HD [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Other research has shown that the introduction of home dialysis, erythropoietin and vitamin D made the quality of life of dialysis patients comparable to kidney transplant recipients. 50 This study shows that biological factors like comorbidities and socioeconomic influences affect a patient's quality of life. Peritoneal dialysis is an alternative option to transplantation in our resource-limited setting as it still provides a good quality of life for patients.…”
Section: Contributions To Literaturementioning
confidence: 93%
“…8 Other research has shown that the introduction of home dialysis, erythropoietin and vitamin D made quality of life of dialysis patients comparable with kidney transplant recipients. 50 This study shows that biological factors like comorbidities and socioeconomic influences affect a patient's quality of life. Peritoneal dialysis is an alternative option to transplantation in our resourcelimited setting as it still provides a good quality of life for patients.…”
Section: Contributions To Literaturementioning
confidence: 93%